The Interplay between L1 and L2 Writing Proficiency - Yonantha, Ferri; Santoso, Nanda Kristia; Taqiyuddin, Taqiyuddin; Retnaningsih, Lina Eka; Hairunnizam, Hairunnizam (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2024)
Today, there is still a combative discussion on the domination of mother tongue (L1) use on second/foreign language acquisition (L2). Particularly, whether or not the use of mother tongue directly affects the ability to write in L2. Experts differ in their opinions on whether mother tongue positively or negatively affects foreign language writing proficiency. This study aims to investigate the interplay between Indonesian (L1) and English (L2) and how significant L1 influences students' ability to write in L2. The case is for Indonesian University context specifically on how L1 applied at pre writing stage could bring some impacts on their English writing. A pre experimental one-group-pre-test-post-test design was employed involving 15 students of English Education Major of a public University in Indonesia as the respondents who were examined through a Purposive Sampling technique. In addition, to analyze the obtain the data of students’ writing proficiency Pre-test and post-test were conducted as research instruments. Finally, the findings showed that the Sig.(2-Tailed) value is 0.001 < 0.05 with the conclusion that there is a significant interplay of the use of Indonesian language on the students' writing ability in English which if represented by 47%.